"You've got to have core muscles": Cultivating hardworking bodies among white-collar women in urban China. (March 2023) - Peng, Xinyan
Drawing on ethnographic fieldwork on young white-collar women training bodies after work in Shanghai, I demonstrate that core muscles serve as visual indexes of discipline and hard-work, and that women create social spaces to collectively cultivate such dispositions. The socially sanctioned value of core muscles is connected to the discourse of 'having it all' increasingly popular among professional women in corporate, urban China. This paper elaborates on how bodily training transposes dispositions of work ethics beyond the workplace and on women's anxieties about their bodies at the intersection of productive and reproductive demands from the society. This paper builds on and critiques existing approaches to the body, and attends not only to the woman's body at the intersection of production and reproduction but also to the social aspect of bodily training in spaces between home and work.